Pemberdayaan UMKM melalui Pengoptimalan Jamur Tiram Menjadi Nugget Dan Sate di Desa Cilapar Kabupaten Purbalingga - El Fathia Raisya Qonitulhaq; Rozan Ghazzali Fattah; Nadyalifa Nabila Putri; Nanda Dwi Putri; Melinda Maharani; Zulfa Putri Kasuwardani; Dimas Reza Aksani; Bagas Pangestu; Alfisyah Putri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Oyster mushroom production, always has a high demand from year to year, but oyster mushrooms are less highlighted by the community, it is proven in the span of 2024, training on the empowerment of oyster mushrooms to become innovative MSMEs in Cilapar Village, does not yet exist, while training on the empowerment of oyster mushrooms as an idea for UMKM, needs to be done, as a solution to the problem of suppressing the unemployment rate. Therefore, the purpose of this research and activity is to elaborate the training of oyster mushroom resources into nuggets and satay in an effort to strengthen UMKM in Cilapar Village as well as a way to handle stunting. The problem that arises is what form of activities are held to realize the idea of nuggets and mushroom satay to the community? The method of implementing this activity is carried out using a qualitative approach. The research data was in the form of oral speech obtained from interview, survey, and observation collection techniques. The results of the activity showed that oyster mushrooms could be processed into nuggets and satay with extraordinary taste, and the level of community activity towards empowering oyster mushrooms into nuggets and satay became high after training, it became a positive encouragement to build a stable economy of the Cilapar Village community